ANALISIS NILAI CBR SEBAGAI PARAMETER KRITIS UNTUK PERENCANAAN JALAN RAYA - Putri Wilis, Sofya Marinda; Cahyono, Andri Dwi; Farihi, Moh. Ilham; Aziz Hanafi, Moh. Abdul; Cintya, Hanifatus; Ibrahim, Malik; Asih, Mia Setiyo (Jurnal Riset Rekayasa Sipil, 2024)
Infrastructure development is one indicator of a country's progress that cannot be ignored. Road infrastructure is an important part of the transportation system that connects different locations, facilitates human mobility, and transports goods. In the construction and maintenance of road infrastructure, soil plays a crucial role, so the condition and strength of the soil must be considered. Soil plays a significant role in construction as it serves as the foundation or base for building structures. Soil that has sufficient strength to support road loads will facilitate road construction. This study was conducted to determine the California Bearing Ratio (CBR) value, so that appropriate actions can be taken to construct roads based on local soil conditions. The CBR method is commonly used in soil geotechnical testing for road planning. This method involves laboratory testing of soil samples to determine the California Bearing Ratio (CBR). The results show a CBR value of 22.5%, which falls under the category of very good. This indicates that there is no need for improvement efforts in the construction of the Jl. Panglima Besar Sudirman, Dsn. Bolawen Ds. Tiron Kec. Banyakan Kab. Kediri highway, allowing resources to be allocated to other areas in need of road infrastructure improvements to enhance accessibility and overall regional development.